Features Of Change In Indicators Of Micro- And Macroelement Status Of The Organism In Women Of Fertilized Age With Anemia Of Iron Deficiency - Akhmedova Nilufar Sharipovna; Sokhibova Ziyoda Rakhmonovna; Ulugova Shakhlo Turaevna (The American Journal of Medical Sciences and Pharmaceutical Research, 2021)
Using unified and developed methods, some hematological, biochemical and indicators of the micro- and macroelement status of the body in Bukhara women of fertile age with a normal hemoglobin health index and iron deficiency have been studied. It has been shown that there are certain pathological fluctuations in some hematological, biochemical and essential hematopoietic microelements in women of fertile age when they develop an iron deficiency state. In particular, there is hypoproteinemia, hypoferremia, hypocincemia, hypocuremia, and hypertransferrinemia. This phenomenon can be used to monitor the state of hemoglobin health in women of fertile age.